(untitled) (Plant Tissue Culture and Biotechnology, 2025)
Rauvolfia tetraphylla, one of the most medicinally important species, belongs to the Apocynaceae family. It produces monoterpenoid indole alkaloids (MIAs) with significant pharmacological value, especially for the treatment of neurological disorders and hypertension. Strictosidine synthase gene (str1), the crucial gene responsible for the production of monoterpene indole alkaloids (MIAs) and its presence substantiates the medicinal value of these plants. In this investigation, we successfully analyzed the tissue-specific (root, stem, and leaf) expression of the str1 gene in different developmental stages (4- and 6-month-old plants) in R. tetraphylla through RT-PCR. Normalized ImageJ analysis showed high str1 expression in roots (1.005 ± 0.005 to 1.152 ± 0.210 ratios), moderate expression in stem (0.242-0.919) and low expression in leaf that decreased with age (from 0.702 ± 0.189 at 4-month-old plants to 0.303 ± 0.384 at 6-month-old plant). Furthermore, we confirmed the target specificity of str1 by sequencing, which showed 94.4-94.56% identity with Rauvolfia str1 homologs. As the first report of str1 expression in Bangladeshi R. tetraphylla, our findings confirm root tissue as the principal site of alkaloid biosynthesis and offer a molecular basis for optimizing cultivation tactics to increase production of its therapeutically valuable compounds. Plant Tissue Cult. & Biotech. 35(1): 129-140, 2025 (June)